Respuesta :
Answer:
Step-by-step explanation:
Isolate the variable by dividing each side by factors that don't contain the variable.
First, simplify both sides of the equation.
- 0.2 (14 - 6y) = - 7y - (- 5 - 9y)
- 0.2 (14 - 6y) = - 7 + - 1 (- 5 - 9y)
− 0.2 (14 − 6y) = − 7y + (− 1) (− 5) + − 1 (− 9y)
− 0.2 (14 − 6y) = − 7y + 5 + 9y
(− 0.2) (14) + (− 0.2) (− 6y) = − 7y + 5 + 9
− 2.8 + 1.2y = − 7y + 5 + 9y
1.2y − 2.8 = (− 7y + 9y) + (5)
1.2y − 2.8 = 2y + 5
1.2y − 2.8 = 2y + 5
Next, subtract 2y from both sides.
1.2y − 2.8 − 2y = 2y + 5 − 2y
− 0.8y − 2.8 = 5
After that, Add 2.8 to both sides.
− 0.8y − 2.8 + 2.8 = 5 + 2.8
− 0.8y = 7.8
Lastly, DIvide both sides by - 0.8
- 0.8y/- 0.8 = 7.8/ - 0.8
y = - 9.75
(Sorry if this is long, it took me a while to type)